Kimberley Whale Coast Tourism: Review of Opportunities and Threats - Hughes, Michael; Catlin, James (The Wilderness Society (WA), 2010)
The Kimberley region covers a vast area of northern Western Australia. Broome is the largest town in the region and in the West Kimberley, which includes Derby, Fitzroy Crossing and numerous discrete Aboriginal communities; it has emerged as that region’s commercial and administrative centre. The expansive Kimberley landscapes and relatively untouched coastal and marine areas, together with vibrant Aboriginal traditional societies and a fascinating colonial heritage, provide the main components of this celebrated nature-based and cultural tourism destination.This report was commissioned by The Wilderness Society WA, the Conservation Council of WA and Environs Kimberley (the ENGOs) to investigate the successful Kimberley tourism ‘brand’, the scope for building on this brand through enhanced marine protection, and the likely impacts on tourism of a largescale heavy industry oil and gas extraction and processing complex in the West Kimberley and Broome coastal and off-shore area. This report is based on desktop analysis using published reports and past research and information from consultations with individuals and organisations based in the region.